SPE Annual Technical Conference and Exhibition 1999
DOI: 10.2118/56721-ms
|View full text |Cite
|
Sign up to set email alerts
|

Downhole Water Sink (DWS) Completion Enchance OIL Recovery in Reservoirs with Water Coning Problem

Abstract: This paper was prepared for presentation at the 1999 SPE Annual Technical Conference and Exhibition held in Houston, Texas, 3–6 October 1999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…It showed that DWS gave better performance of water coning control and higher oil production rates than conventional wells, which were confirmed by successful field implementations by Hunt Petroleum several other companies Wojtanowicz, 1995a, 1995b;Bowlin et al, 1997;Loginov and Shaw, 1997). Both physical and numerical experiments showed that DWS could improve oil recovery in terms of recovery factor and time in view of total production of liquids (oil and water) from reservoirs (Shirman, 1998;Kurban, 1999;Wojtanowicz, et al, 1999). However, one of the drawbacks of DWS is that, it needs to drain a huge amount of water to the surface when there is no disposal zone in the reservoir.…”
Section: Introductionmentioning
confidence: 73%
“…It showed that DWS gave better performance of water coning control and higher oil production rates than conventional wells, which were confirmed by successful field implementations by Hunt Petroleum several other companies Wojtanowicz, 1995a, 1995b;Bowlin et al, 1997;Loginov and Shaw, 1997). Both physical and numerical experiments showed that DWS could improve oil recovery in terms of recovery factor and time in view of total production of liquids (oil and water) from reservoirs (Shirman, 1998;Kurban, 1999;Wojtanowicz, et al, 1999). However, one of the drawbacks of DWS is that, it needs to drain a huge amount of water to the surface when there is no disposal zone in the reservoir.…”
Section: Introductionmentioning
confidence: 73%
“…6 While theoretically the total water cut (the sum from both the top and bottom completions) could also be reduced, in actuality this is hard to attain due to the limiting ability to perfectly design and "tweak" a DWS completion system unique to an individual well and/or reservoir. 7 If more oil is produced quicker (higher flow rates with increased recovery of the initial oil in place (IOIP)) sufficient enough to surpass the normal expenditures, plus the added expenditures required for a DWS system, the project has an increased economic benefit.…”
Section: Geologic Analysis Overviewmentioning
confidence: 99%
“…The size of the reservoir and the remaining reserves must also be considered. Wojtanowicz et al proposed six (6) basic structures and systems that should be considered for the applicability of a DWS system. 9 The structures are as follows:…”
Section: Geologic Analysis Overviewmentioning
confidence: 99%
“…Downhole Water Sink (DWS) is a technique for producing water-free hydrocarbons from reservoirs with bottomwater drives and strong tendencies toward water coning (9)(10)(11)(12)(13)(14)(15) . Conventional wells in these reservoirs produce increasing volumes of brine with decreasing amounts of oil or gas ( Figure 2) which ultimately leads to early shut-down of these wells without sufficient recovery of hydrocarbons in place.…”
Section: Principles Of Dwsmentioning
confidence: 99%